مدى التزام المصارف التجارية السورية الخاصة بالعوامل المحددة لقرار منح الائتمان المصرفي: دراسة ميدانية - نادر, نهاد; نعنوع, رولا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The research aims to study the extent of Syrian commercial banks' commitment to the determinants of bank credit to grant, get out a set of proposals that would Syrian commercial banks own departments in general benefit, credit management, in particular to the need to adhere to the specific factors for granting credit facilities in order to avoid falling into the risks of non-payment , or bank defaults. Find the descriptive method, and the method of scanning adopted, where used questionnaire as the main source to obtain data, and be community study all employees responsible for bank credit in the Syrian private commercial banks, where the method was used comprehensive inventory in their opinions about the role of the specific decision of credit factors banking performance, in the provinces of Damascus and Latakia and Tartous, due to the current circumstances. Consequently it was distributed (175) to identify the workers, and was re-ones (163) questionnaire complete and valid for statistical analysis, and response rate (93.14%). The results showed that in the study of commercial banks will query for specific grants credit decision factors, was the order of these factors according to the following: factors relating to credit the subject, factors related to the head of client money, factors related to the personality of the client, the factors related to the ability of the client, factors related to general and specific circumstances surrounding customer, factors relating to the guarantees provided by the client, the factors related to the bank. هدف البحث إلى دراسة مدى التزام المصارف التجارية السورية بالعوامل المحددة لمنح الائتمان المصرفي, والخروج بمجموعة من المقترحات التي من شأنها أن تفيد إدارات المصارف التجارية السورية الخاصة بشكل عام, وإدارة الائتمان بشكل خاص من خلال الالتزام بالعوامل المحددة لمنح التسهيلات الائتمانية تفادياً لوقوعها في مخاطر عدم السداد, أو التعثر المصرفي. اعتمد البحث على المنهج الوصفي, وأسلوب المسح, حيث اُستخدمت الاستبانة كمصدر رئيس في الحصول على البيانات, وتكون مجتمع الدراسة جميع العاملين المسؤولين عن الائتمان المصرفي في المصارف التجارية السورية الخاصة المدروسة, حيث تمّ استخدام طريقة الحصر الشامل في استطلاع آرائهم حول دور العوامل المحددة للقرار الائتماني في الأداء المصرفي, وذلك في محافظات دمشق, واللاذقية وطرطوس بسبب الظروف الراهنة. وبناءً على ذلك تمّ توزيع (175) استبانة على العاملين, وأعيد منها (163) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (93.14%). وأظهرت النتائج أنّ المصارف التجارية محل الدراسة تستعلم عن العوامل المحددة لمنح القرار الائتماني, وقد كانت ترتيب هذه العوامل وفق الآتي: العوامل المتعلقة بموضوع الائتمان, العوامل المتعلقة برأس مال العميل, العوامل المتعلقة بشخصية العميل, العوامل المتعلقة بمقدرة العميل, العوامل المتعلقة بالظروف العامة والخاصة المحيطة بالعميل, العوامل المتعلقة بالضمانات المقدمة من العميل, العوامل المتعلقة بالمصرف.